A Bayesian Network Meta-Analysis for Identifying the Optimal Taxane-Based Chemotherapy Regimens for Treating Gastric Cancer - Zhang, Dan; Wu, Jia-Rui; Duan, Xiao-Jiao; Wang, Kai-Huan; Zhao, Yi; Ni, Meng-Wei; Liu, Shu-Yu; Zhang, Xiao-Meng; Zhang, Bing (Frontiers in Pharmacology, 2019)
Background: Several taxanes-based chemotherapy regimens were effective in the treatment of gastric cancer; nevertheless, their comparative efficacy and safety still remain disputed. This network meta-analysis (NMA) was designed to compare the efficacy and safety of different taxanes-based chemotherapy regimens against gastric cancer. Methods: A comprehensive search was conducted to identify all relevant randomized controlled trials (RCTs) in multiple electronic databases. Bayesian network meta-analysis was performed to combine the direct and indirect evidence and estimate the comparative efficacy and safety of different taxanes-based chemotherapy regimens simultaneously by utilizing WinBUGS 1.4.3 and Stata 13.1 software. The efficacy outcomes included overall survival rate (OS), progression-free survival (PFS) and overall response rate (ORR); and the safety outcomes were adverse reactions (ADRs), namely neutropenia, leucopenia, vomiting and fatigue. Results: A total of 37 RCTs were identified involving 7178 patients with gastric cancer, and 10 taxanes-based chemotherapy regimens (RT, T, TC, TCF, TF, TO, TOF, mTCF, mTF, mTOF) were collected in gastric cancer therapy. According to the results of cluster analysis, the regimen of TOF, mTCF, TF were associated with the most favorable clinical efficacy in improving OS, PFS and ORR than other taxanes-based chemotherapy regimens. On the other hand, the regimen of T and mTF had the potential to be most tolerable and acceptable therapeutic alternative in terms of ADRs.. Conclusions: The current NMA provide the evidence that the combination of taxanes (paclitaxel or docetaxel) and fluorouracil was associated with the most preferable and beneficial option for patients with gastric cancer, although the additional results from multi-center trials and high-quality studies will be pivotal for supporting our findings.